2013
DOI: 10.1021/ic401450u
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation-Potential Tuning of Tungsten–Alkylidyne Complexes over a 2 V Range

Abstract: The electrochemistry and electronic structures of over 30 tungsten-alkylidyne compounds of the form W(CR)L(n)L'(4-n)X (R = H, Bu(t), Ph, p-C6H4CCH, p-C6H4CCSiPr(i)3; X = F, Cl, Br, I, OTf, Bu(n), CN, OSiMe3, OPh; L/L' = PMe3, 1/2 dmpe, 1/2 depe, 1/2 dppe, 1/2 tmeda, P(OMe)3, CO, CNBu(t), py), in which the alkylidyne R group and L and X ligands are systematically varied, have been investigated using cyclic voltammetry and density functional theory calculations in order to determine the extent to which the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(53 citation statements)
references
References 137 publications
8
45
0
Order By: Relevance
“…Interestingly, the orbital participates in the one electron oxidation process is the d xy (HOMO) orbital of W atom and the calculated HOMO orbital energies of these various complexes are linearly correlated with the experimental redox potentials. By altering the coordinating ligands, the electronic properties of the metal center can be fine-tuned and the expected redox properties can be obtained [134]. Similar to this study, the calculated redox potentials using the B3LYP method in water and DMSO solvents, produced excellent correlations with respect the HOMO and LUMO orbital energies for a number of Cu complexes [135].…”
Section: Transition Metal Complexessupporting
confidence: 66%
See 1 more Smart Citation
“…Interestingly, the orbital participates in the one electron oxidation process is the d xy (HOMO) orbital of W atom and the calculated HOMO orbital energies of these various complexes are linearly correlated with the experimental redox potentials. By altering the coordinating ligands, the electronic properties of the metal center can be fine-tuned and the expected redox properties can be obtained [134]. Similar to this study, the calculated redox potentials using the B3LYP method in water and DMSO solvents, produced excellent correlations with respect the HOMO and LUMO orbital energies for a number of Cu complexes [135].…”
Section: Transition Metal Complexessupporting
confidence: 66%
“…The obtained slope values from these fitted lines showed a non-dependent behavior with respect to the metals, this confirms that the determined parameters are ligand specific [133]. Redox potentials for 30 octahedral tungsten-alkylidyne complexes with a variety of different coordinating ligands were calculated by employing the hybrid B3LYP DFT method [134]. Interestingly, the orbital participates in the one electron oxidation process is the d xy (HOMO) orbital of W atom and the calculated HOMO orbital energies of these various complexes are linearly correlated with the experimental redox potentials.…”
Section: Transition Metal Complexessupporting
confidence: 66%
“…13−16 The covalently bonded and electronically delocalized bridging π ligand acts as a structurally well-defined rigid-rod intramolecular electron pathway, and by successively varying the metal center(s) 17 and the bridging 18 and nonbridging ligands, 19 it is possible to probe the relationship between molecular structure and spectroscopic and electrochemical properties. It was shown that the electronic delocalization extends over the length of the organometallic unit in most cases.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These luminescent chromophores possess long-lived 3 A C H T U N G T R E N N U N G [(d xy ) 1 (p*-A C H T U N G T R E N N U N G (WCR)) 1 ] excited states (t em = 10 2 -10 3 ns), [8] are powerful photochemical reductants (E* / + < À2 V vs. FeCp 2 0/ + ) with small reorganization energies, [9] and their ground-state (d xy ) 2 /A C H T U N G T R E N N U N G (d xy ) 1 oxidation potentials are systematically tunable across a 2 V range through ligand variation. [10] As a result, these chromophores are well suited for photosensitizing a wide range of electroactive catalysts for difficult-to-reduce substrates, such as CO 2 . Further, unlike common transitionmetal chromophores, [W(CR)L 4 Excitation of the porphyrin-centered S 1 excited states of these dyads initiates intramolecular energy-transfer (ZnPor!1) and electron-transfer (1!…”
Section: Introductionmentioning
confidence: 99%
“…One class of compounds that possesses the properties to fulfill these requirements is that of (d xy ) 2 ‐configured tungsten–alkylidyne compounds of the type trans ‐[W(≡CR)L 4 X] (R=aryl, L=neutral ligand, X=anionic ligand). These luminescent chromophores possess long‐lived 3 [(d xy ) 1 (π*(WCR)) 1 ] excited states ( τ em =10 2 –10 3 ns),8 are powerful photochemical reductants ( E * /+ <−2 V vs. FeCp 2 0/+ ) with small reorganization energies,9 and their ground‐state (d xy ) 2 /(d xy ) 1 oxidation potentials are systematically tunable across a 2 V range through ligand variation 10. As a result, these chromophores are well suited for photosensitizing a wide range of electroactive catalysts for difficult‐to‐reduce substrates, such as CO 2 .…”
Section: Introductionmentioning
confidence: 99%